Мар луоз ӵуказе?: веросъёс но пьеса / Ульфат Бадретдинов - Бадретдинов Ульфат Шайхутдинович (1991)
Экземпляры: ф.1 (20181221) / Инвентарный номер: 25136 / Цена: 2.00 / Авт.знак: Б 15 / ГРНТИ: 17.82 / ББК: 84 (2Рос.Удм)6